L’échec des corps de contrôle comme cause profonde de la crise institutionnelle en Haïti - Bénédique Paul (Études Caribéennes)
Most of the repeating crises in Haiti have their source in a deeper one, the institutional crisis. In this article, we discuss the concept of institutional crisis and analyse this phenomenon at the level of the constituted bodies supposed to guarantee social control and ensure development. The approach by the bodies of control mobilized is inspired by the concept of Instituted Third Party proposed by Pierre Legendre. As much as it is true that one can only give what one has, it is also true that institutional crisis within the constituted bodies can explain institutional crisis at the Statehood. The institutional analytical framework represented by the Instituted Third Party offers not only an opportunity for a fruitful analysis of the crisis, but also a possible effective strategy for resolving it.